PENERAPAN METODE PEMBELAJARAN INQUIRY PADA MATA PELAJARAN PPKn SISWA KELAS XI IPS SMA PANCA BHAKTI PONTIANAK - Abl, Peni; Utomo, Bambang Budi; Sastratamaja, Thomy (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractÂ This study was aimed to determine the Application of Inquiry Learning Methods in PPKn Subjects of Class XI IPS Students of Panca Bhakti High School Pontianak. Which consists of one class as a research sample by using learning outcomes observation sheets (pre-test and post-test) observation sheet of student activities and student response questionnaires. Data analysis techniques used descriptive and inferential statistical analysis techniques. Descriptive statistical analysis of the result of the study showed: (1) The average learning achievement used the inquiry learning method with settings was 3.9 (very good), (2) the initial average of students' ability (pre-test) was 45.76 in the very category low. The average learning achievement students (post-test) was 88.67 in the high category, (3) the result of classical completeness post-test reached 100% (30 students) achieved individual mastery, (4) the average normalized profit was 0.79 which was at high category, (5) the average percentage of student activity was 92%, (6) the average percentage of students who give positive responses to the application of learning was 94%.Â Keywords: application of the method, Inquiry LearningÂ